Mapping genomic regions for reproductive stage drought tolerance in rice from exotic landrace-derived population - Venkateshwarlu, Challa; Kole, Paresh Chandra; Singh, Arun Kumar; Paul, Pronob J.; Sinha, Pallavi; Singh, Vikas Kumar; Kumar, Arvind (Frontiers in Plant Science, 2025)
In the rapid climate change scenario and subsequent rainfall patterns, drought has emerged as a bottleneck for crop production across crops, especially in rainfed rice. Drought significantly affects the development and production of most modern rice cultivars. Thus, recent breeding efforts have aimed to integrate drought tolerance traits in existing rice varieties through conventional and molecular approaches. The identification of grain yields quantitative trait loci (QTLs) under drought conditions, an important trait with high selection efficiency, may lead to the development of drought-tolerant rice varieties. The study reported the grain yield QTLs identified under the reproductive stage of drought stress in the F2-derived mapping population from Kasturi (drought-sensitive) × Chao Khaw (drought-tolerant). Thirteen QTLs (qDTYs) were identified based on two years of field data. Comparative analysis revealed two robust and consistent DTY QTLs, qDTY1.1 and qDTY8.1, which explained the PVEs of 11.61% to 12.88% and 15.79% to 18.77%, respectively. However, qDTY1.1 was found at the nearest position to the previously identified qDTYs. Through candidate gene analysis, the identified QTL regions in chromosome 1 (qDTY1.1) and chromosome 8 (qDTY8.1) revealed seven and five candidate genes, respectively, based on gene ontology that were significantly associated with rice grain yield-related drought traits. In conclusion, this study identified key consistent drought yield QTLs in a drought-tolerant exotic landrace. The identified QTLs provide valuable insights and resources for ongoing efforts to develop drought-tolerant rice varieties. They can be further utilized in drought breeding programs to enhance the drought resilience of existing varieties or to develop new varieties.